PERANCANGAN SISTEM INFORMASI PELAYANAN PUBLIK PADA RUKUN WARGA 05 CENGKARENG TIMUR DENGAN PENERAPAN METODE NAÏVE BAYES - Meliana Meliana; Riri Fajriah (Sekolah Tinggi Teknik - PLN, 2019)
Public service is a service provided by the government as the state administrator of the community to meet the needs of the community itself and has a purpose to improve the welfare of the community. The forms of service that are in the neighborhood of Citizenship 05 include basic administrative services,for example:services for making Family Cards, Birth Certificates, Death Letters, KTPs, Not Available Certificate (SKTM) and many others. The problem faced by the pillars of 05 is the administration and bureaucracy that have not been computerized, causing public services to be long. In addition, there are still many public service irregularities in the Rukun Warga 05, especially in the deviation from giving an insufficient certificate. Previous research on poor SKTM recipients in Jambi City was one of the bases of this research. The design of the public service information system in the RW 05 area was designed using several modules, namely the citizen reporting module, RW work program evaluation module, RT work program distribution module, citizen administration module, evaluation of SKTM giving, socialization module and citizen information. The implementation of this public service uses a prototype method and uses PIECES analysis with the application of naive bayes for selection of inadequate certificates so that public services and the provision of SKTM can be done effectively, efficiently and on target.